2009
DOI: 10.1098/rsif.2008.0539
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond histology. Synchrotron micro-computed tomography as a methodology for biological tissue characterization: from tissue morphology to individual cells

Abstract: Current light microscopic methods such as serial sectioning, confocal microscopy or multiphoton microscopy are severely limited in their ability to analyse rather opaque biological structures in three dimensions, while electron optical methods offer either a good three-dimensional topographic visualization (scanning electron microscopy) or high-resolution imaging of very thin samples (transmission electron microscopy). However, sample preparation commonly results in a significant alteration and the destruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 34 publications
0
65
0
Order By: Relevance
“…Moreover, if we assume that high-resolution refers to the ability to resolve features on the nanometre scale, then, in fact, only electron and atom probe tomography meet this constraint. Even synchrotron source X-ray computed tomography, regularly employed in the characterization of biomaterials and their tissue interfaces, generally provides resolution in the micrometre range [7,8], albeit recent advances and specialized instrumentation have pushed the resolution into the nanometre regime [9]. Perhaps the highest resolution tomographic technique, atom probe tomography, enables atomic resolution in three dimensions.…”
Section: Tomographic Techniquesmentioning
confidence: 99%
“…Moreover, if we assume that high-resolution refers to the ability to resolve features on the nanometre scale, then, in fact, only electron and atom probe tomography meet this constraint. Even synchrotron source X-ray computed tomography, regularly employed in the characterization of biomaterials and their tissue interfaces, generally provides resolution in the micrometre range [7,8], albeit recent advances and specialized instrumentation have pushed the resolution into the nanometre regime [9]. Perhaps the highest resolution tomographic technique, atom probe tomography, enables atomic resolution in three dimensions.…”
Section: Tomographic Techniquesmentioning
confidence: 99%
“…This in turn leads to noisy and artefact-corrupted reconstructed three-dimensional images. There are a number of studies reported where hard X-rays are used for tomographic image reconstruction that penetrate tens of micrometres into tissues and cell clusters, but these methods achieve much lower spatial resolution (micrometre range) than using the SXT method described here [48][49][50].…”
Section: Transmission Soft X-ray Microscopymentioning
confidence: 99%
“…Later on, this chapter deals with approaches using stacks of polymer sheets for possible applications in neuronal tissue engineering. Fig.2 has been used predominantly in this chapter and is described in several studies (Zehbe 1 et al, 2007;Zehbe 1 et al, 2009;Rack et al, 2008). Although the photon flux density is several orders of magnitude higher than in X-ray tubes, it is not constant over the X-ray energy.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…While imaging in absorption contrast is well adapted to samples featuring a prominent difference in density or atomic mass, phase contrast imaging allows detection of structural details which are not well visible in absorption. Here, the contrast is achieved by retardation or refraction of coherent X-rays at phase boundaries inside the sample (Cloetens et al, 2006;Rack et al, 2008;Zehbe 1 et al, 2009). Fig.…”
Section: Tissue Engineering 340mentioning
confidence: 99%